SOCIAL BRIDGES INTERGENERATIONAL HOUSING - Sterner, Beatrice (My University, 2023)
The aim of this thesis is to investigate the issues of an aging society and the growing need for alternative housing solutions to meet those demands. It discusses the issues of ageism and the lack of meetings between different generations. Further, the thesis responds to the issues of young adults not finding affordable and appropriate housing alternatives. The thesis proposes the implementation of a new housing model that combines sheltered housing, housing for young adults, and a nursing home while integrating a school and the community. The proposal is a housing project where intergenerational meetings naturally occur in order to prevent ageism. The thesis opted for an exploratory approach with theory as its core. The theory is based on research papers, articles, books, and reference projects. Literature studies are complemented by an interview with an architect who has done extensive research within the field of intergenerational housing, an interview with two experts on the subject of intergenerational practice, as well as a study visit to an intergenerational housing project in Helsingborg. The thesis provides insights into how you can implement different levels of shared and public spaces in a housing project in order to provide opportunities for intergenerational meetings. Further, it suggests architectural implementations in order to create a sense of home while enabling accessibility into the regular apartment as standard in order to create flexibility within the housing market. This is primarily a conceptual approach to these issues and may lack enough insight into the economy, policies, and politics. Therefore, the research could be developed further with these areas in mind. This paper fulfills an identified need to develop new alternative housing solutions where the intention is that intergenerational meetings are promoted and valued.
Keywords: Intergenerational housing, communal housing, sense of home